2008
DOI: 10.1103/physrevb.78.035316
|View full text |Cite
|
Sign up to set email alerts
|

Turn-on dynamics and modulation response in semiconductor quantum dot lasers

Abstract: We show that the dynamic response of electrically pumped semiconductor quantum dot lasers can be quantitatively understood by including the strongly nonlinear character of electron-electron scattering processes. The numerical simulations presented here combine a microscopic approach used for calculating the nonradiative scattering rates with a rate equation model used for modeling the complex dynamic turn-on behavior. Simulated turn-on delay, relaxation oscillation frequency, small-signal modulation response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 32 publications
5
49
0
Order By: Relevance
“…It is known from previous studies that QD lasers exhibit a certain number of properties that make them attractive for application [6]. A particularly attractive property is an unusually high damping of the ROs [18] in comparison to their bulk and quantum well (QW) counterparts. This high damping has been cited as the principal reason for the increased stability of such devices subject to optical feedback [21], optical injection [8,10,14], and mutual coupling [12,15] configurations.…”
Section: Introductionmentioning
confidence: 99%
“…It is known from previous studies that QD lasers exhibit a certain number of properties that make them attractive for application [6]. A particularly attractive property is an unusually high damping of the ROs [18] in comparison to their bulk and quantum well (QW) counterparts. This high damping has been cited as the principal reason for the increased stability of such devices subject to optical feedback [21], optical injection [8,10,14], and mutual coupling [12,15] configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The QD hole density is changing more slowly as compared to the electron density [16]. Desynchronized carrier dynamics results in the deterioration of the laser performance both in the small-signal and in the large-signal regimes [15,17]. In particular, the QDWELL laser modulation frequency is limited by the RO frequency of 7 GHz [17].…”
Section: Structure and Operation Principle Of A Semiconductor Lasermentioning
confidence: 99%
“…The turn-on dynamics, the small signal and large signal responses of a QDWELL laser have been studied theoretically and experimentally in the fundamental works of Lüdge, Schöll and co-workers [10,[13][14][15][16][17][18].…”
Section: Structure and Operation Principle Of A Semiconductor Lasermentioning
confidence: 99%
“…Over recent decade, considerable efforts have been devoted to investigate the main reasons of damped modulation bandwidth in QD diode lasers including carrier dynamics at different states of QD lasers or coulomb interaction [11], [13]. For instance, Wang et al have demonstrated that the finite carrier transitions through wetting layer (WL) as well as the Pauli blocking can result in limitation of the QD laser modulation bandwidth [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, they are predicted to show superior characteristics which are profoundly attractive for high speed optical communications [2]- [8]. Although, recent experimental researches have demonstrated QD lasers with low threshold current at room temperature [3], high temperature stability [4]- [6], and low frequency chirping [7]- [8], the modulation response of QD lasers have shown damped relaxation oscillations with restricted bandwidth up to 10 GHz [9]- [11].…”
Section: Introductionmentioning
confidence: 99%